1995
DOI: 10.1111/j.1525-1314.1995.tb00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic and structural history of continental crust at a Mesozoic collisional margin, the Ruby terrane, central Alaska

Abstract: The Ruby terrane is an elongate fragment of continental crustal rocks that is structurally overlain by thrust slices of oceanic crust. Our results from the Kokrines Hills, in the southcentral part of the Ruby terrane, demonstrate that the low-angle schistose fabric formed under high-P /low-T conditions, at peak conditions of 10.8-13.2 kbar and 425-550" C, consistent with the rare Occurrence of glaucophane. White mica 40Ar/39Ar cooling ages from these blueschists indicate that the metamorphism occurred prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The major difference between the two regions is the 784 presence of late Early Cretaceous (118-109 Ma; Roeske et al, 1995;Roeske et al, 1998; 785 this study) granites and granodiorites that intrude older rocks of the Ruby terrane. The 786 composition of Type 2 sediments combined with their detrital zircon U-Pb ages suggest 787 they were likely derived from both the southern Brooks Range and Ruby terrane.…”
Section: Ruby Batholith 782mentioning
confidence: 78%
See 3 more Smart Citations
“…The major difference between the two regions is the 784 presence of late Early Cretaceous (118-109 Ma; Roeske et al, 1995;Roeske et al, 1998; 785 this study) granites and granodiorites that intrude older rocks of the Ruby terrane. The 786 composition of Type 2 sediments combined with their detrital zircon U-Pb ages suggest 787 they were likely derived from both the southern Brooks Range and Ruby terrane.…”
Section: Ruby Batholith 782mentioning
confidence: 78%
“…to Paleozoic 295 metasedimentary rocks and minor metabasite and quartzofeldspathic gneiss (Dover, 296 1994;Moore and Box, 2016). Thermobarometry by Roeske et al (1995) identified an 297 14 overprinted by greenschist facies assemblages. In the western Kokrines Hills portion of 299 the Ruby terrane, metamorphic assemblages document a later upper amphibolite to lower 300 granulite facies event that likely overprinted the earlier HP metamorphic fabric in the late 301…”
Section: Ruby Terrane 292mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Taylor Highway Map area in Alaska near the Canadian border shows much older 40 Ar/ 39 Ar dates-187 to 213 Ma for hornblende, 109 to 204 Ma for biotite, and 109 to 191 Ma for muscovite (Cushing, 1984;DuselBacon et al, 1989). Dusel-Bacon et al (1995) speculated that underthrusting of the North American continent beneath the Nistling microcontinent formed the A-type blueschist belt, and regarded 166 to 204 Ma 40 Ar/ 39 Ar ages to be cooling ages. The estimated P/T conditions range from 10 kbar, 450° C to 17 kbar, 700° C for high-temperature blueschist and eclogite (Hansen et al, 1991;Hansen, 1992), which clearly belong to the jadeite-glaucophane-type facies series, as documented by the low-temperature assemblages (Paterson and Harakal, 1974).…”
Section: North Americamentioning
confidence: 99%